The Effect of Telehealth Based on Symptom Control and Rational Medication Use on Self-Efficacy, Anxiety-Depression, and Symptoms in Male Patients with COPD: A Quasi-Experimental Study - Şenay Takmak; Nevin Kuzu Kurban (Galician Medical Journal)
Introduction. Chronic obstructive pulmonary disease (COPD) is a critical global public health issue, imposing substantial physical, social, and economic burdens due to its symptoms and exacerbations. Telehealth has the potential to be applied for symptom management, monitoring medication adherence, and providing psychological support.